Assessing the Role of Information and Communication Technology (ICT) as a Tool for Organizational Communication - Abdu, Khalid Fatima; Idris, Zago Salisu; Binni, Muhammad Amina (Darul Yasin Al Sys, 2025)
This study examines the role of Information and Communication Technology (ICT) as a critical enabler of organizational communication, with a focus on its implementation within a commercial bank in Nigeria. ICT encompasses a wide range of technologies used for the processing and dissemination of information, and its integration has profoundly influenced communication practices, organizational structures, and managerial operations across various sectors. Within organizational contexts, ICT tools such as computers, telephones, email, databases, video conferencing, and search engines have significantly enhanced internal and external communication efficiency. This study aims to assess the extent to which ICT facilitates organizational communication and supports collaboration, information dissemination, and employee engagement. A structured questionnaire was randomly distributed among employees of the selected bank, and the collected data were analyzed using descriptive statistics, including mean scores and percentages, with the aid of SPSS software. The results indicate a positive perception of ICT’s role in enhancing communication processes, boosting employee morale, supporting collaboration, and contributing to the achievement of organizational goals. These findings underscore the strategic importance of ICT in modern organizational communication and highlight the need for continued investment in technological infrastructure to improve communication effectiveness and overall organizational performance.